Applying Production Capacity Planning Analysis to Enhance Operational Efficiency in the Garment Industry - Novalia Dwi Pratama, Cindy; Yuliawati, Evi (UNIPA PRESS, 2025)
Rira Clothing Convection is a business engaged in convection by producing Muslim clothes for girls. The demand to always be dynamic in adjusting to the development of fashion trends on a regular basis shows the company's awareness of the importance of adapting to the ever-changing market. The existence of these fluctuations certainly affects the production process which includes the target number of clothes that must be produced, the determination of the number and schedule for ordering raw materials, the production process time, the number of machines needed and others. The purpose of this study is to minimize the cost of raw material inventory with the Material Requirement Planning (MRP) Method and plan the optimal production capacity so that production runs effectively and efficiently with the Capacity Requirement Planning (CRP) Method. The results of the study obtained that the calculation of the minimum inventory used the Material Requirement Planning (MRP) method with the Economic Order Quantity (EOQ) technique. The total inventory cost for the main raw materials is Diamond Crepe fabric with four orders of 427.5 meters/order and Rayon Stretch fabric with three orders of 745.5 meters/order of Rp 1,400,000. The optimal production capacity planning is the number of working days at the pattern making, cutting and sewing stations as many as four days in five periods and 4.5 days in one period, while in the bundling, packing and finishing stations as many as four days in six periods.